Factors influencing Gleason score up/downgrade in radical prostatectomy - Zafer Gokhan Gurbuz; Umut Unal; Ediz Vuruskan; Mubariz Aydamirov; Kadir Karkin (BMC Urology)
Abstract Purpose To evaluate the preoperative and pathological gleason score (GS) concordance rates and biopsy, pathological and clinical parameters that may cause discordance in patients who underwent radical prostatectomy (RP) for prostate cancer (PCa) in a single tertiary referral center. Patients and methods The data for patients who underwent RP due to PCa were retrospectively scanned after obtaining approval from the local ethics committee. Preoperative age, total PSA value, prostate volume, PSA density, PI-RADS score, digital rectal examination findings, biopsy type and pathological parameters after RP were evaluated in terms of GS concordance. Upgrading or downgrading was defined as an increase or decrease from one GS group to another. Results While preoperative and pathological GS were concordant in 151 patients (56.1%), values in 118 patients (43.9%) were found to be discordant. Of the 118 patients with preoperative and pathological discordance, 41 patients (34.7%) were downgraded, and 77 patients (65.3%) were upgraded. When preoperative and pathological GS concordance is compared, International Society of Urological Pathology grade group, D’Amico risk classification and clinical stage affected downgrading or upgrading of patients. In the presence of perineural, lymphovascular, seminal vesicle invasion and positive surgical margins in pathological examinations, GS discordance increased (p = 0.020, p = 0.003, p = 0.006 and p = 0.003, respectively). Conclusions According to the results of our study, one out of every two patients who underwent RP due to PCa had preoperative and pathological GS discordance.